PENGARUH TARI KREASI PADA PERKEMBANGAN MOTORIK KASAR PADA ANAK USIA 5- 6 TAHUN - Qolbi, Ahsana Zaida; As Zahra Lubis, Sandrina; Khairani, Indah; Munadi, Khairani; Zahra Lubis, Hilda (Pimpinan Cabang Muhammadiyah Kramat Jati, 2024)
Gross motor skills are abilities that are needed from toddler age as part of a child's growth and development. Gross motor skills are built from the time they are toddlers and will get better with age until adulthood. As time goes by, the benefits of gross motor skills for children are being able to control their body movements. Research using the library research method is research that uses methods to obtain information data by placing existing facilities in the library such as books, magazines, documents, records of historical stories or pure library research related to the research object